Pengaruh Musik Klasik Terhadap Kecemasan Matematika dan Dampaknya Pada Prestasi Belajar Matematika Peserta Didik Kelas XB SMK Negeri 2 Kasihan Bantul (SMM) (International Forum of Researchers and Lecturers, 2024)
This research aims to find out how classical music influences the level of mathematics anxiety of class XB students at SMK Negeri 2 Kasihan Bantul. Second, what is the impact of classical music on the mathematics learning achievement of class XB students at SMK Negeri 2 Kasihan Bantul. The research subjects were class XB students at SMK Negeri 2 Kasihan Bantul with a total of 17 students. The type of research used is quantitative research supported by a qualitative approach. The research instruments used in the research were questionnaires, ability tests, and observations. The data obtained was analyzed quantitatively and qualitatively. The results of the research show that classical music has an effect on reducing the level of mathematics anxiety of class XB students at SMK Negeri 2 Kasihan Bantul. Then classical music had an impact on improving the mathematics learning achievement of class XB students at SMK Negeri 2 Kasihan Bantul.